1, 2, 3-Triazole based poly(ionic liquids) as solid dielectric materials. (6th January 2021) - Niskanen, Jukka; Tousignant, Mathieu N.; Peltekoff, Alexander J.; Lessard, Benoît H.
Abstract: 1, 2, 3-triazole based polyionic liquids (PIL) are an emerging field among polymeric dielectrics in organic electronics. 1, 2, 3-triazole based PILs can be obtained from poly(4-vinylbenzylchloride) by copper-catalyzed azide-alkyne cycloaddition (CuAAC) 'click' reaction. The polymer architecture and the charge of the PILs can be manipulated by choosing a suitable alkyne, azide containing moiety, and by the alkylation of the 1, 2, 3-triazole group. Thus, we were able to prepare PILs carrying either inorganic (Na + or Cl − ) or the organic counterions 1-butyl-3-methyl-imidazolium (C4mim + ) or 1-butyl-3-methyl-imidazolium (TFSI − ). Metal-insulator-metal capacitors were fabricated and the dielectric properties were characterized through electrochemical impedance spectroscopy. The PILs demonstrated an increase in capacitance density with decreasing frequency, characteristic for the polarization of the polymer layer and electrical double layer formation. Substitution of inorganic counterions with organic counterions improved the transition frequency of the capacitors and the conductivity of the polymers. This was due to increased ion mobility and decreased glass transition temperatures. Graphical abstract: Image 1 Highlights: 1, 2, 3-triazole based polyionic liquids (PIL) are an emerging field among polymeric dielectrics in organic electronics. Copper-catalyzed azide-alkyne cycloaddition (CuAAC) was used to prepare 1, 2, 3-triazole PILs from poly(vinylbenzylchloride). PIL charge and properties can be manipulated by choosing the correct alkyne. Characteristic electrical double layer formation was observed by electrochemical impedance spectroscopy. Capacitors made from the PILs demonstrated an increase in capacitance density with decreasing frequency.